Qualidade de vida relacionada à saúde em pacientes acometidos por doença inflamatória intestinal tratados com terapia biológica - Silva, Isabel Cristina Lopes da [UNESP] (2015)
Inflammatory bowel diseases are becoming a major public health problem in Brazil and worldwide. Although their incidence is relatively low, studies show that young people of working age are affected by this disease characterized by periods of activity and remission amending of impactful quality of life. The conventional medical treatment includes the use of immunosuppressive and immunoregulatory agents.It stands out among these treatments biological therapy, represented by the class of tumor necrosis drugs (anti-TNF α). Objective: To correlate the clinical response to the quality of life of patients with inflammatory disease treated with biologic therapy. Methods: A prospective longitudinal study conducted at the Hospital of the Botucatu School of Medicine / UNESP, which evaluated 35 patients with inflammatory bowel disease using biological therapy through Inflammatory quality of life questionnaires Bowel Disease Questionnaire(IBDQ) and Crohn's disease activity index (DC), and CDAI score of Mayo for Ulcerative Colitis and Montreal Rating disease at weeks 0, 14,30,54 Results: 42,8% of the study population were female, 57,2% male, 94,3% white, 17,1% were smokers, and 77,1% were affected by Crohn's disease (CD) and 22.8% Colitis Colitis (UC). Of these patients 65, 7% made use of Infliximab and 34,3% of Adalimumab. The mean disease duration was 6,1 years (± 5,0). Clinical remission with symptom improvement and healing of the intestinal mucosa was achieved by 80% of patients. Perianal manifestations were observed in 44,4 %%, 25,7% required hospitalization, surgery 25,7%, 2,9% progressed to death. In responding patients showed a statistically significant improvement in all the applied life quality scores